2018
DOI: 10.1007/s11356-018-1734-7
|View full text |Cite
|
Sign up to set email alerts
|

Non-point source pollution of glyphosate and AMPA in a rural basin from the southeast Pampas, Argentina

Abstract: We measured the occurrence and seasonal variations of glyphosate and its metabolite, aminomethylphosphonic acid (AMPA), in different environmental compartments within the limits of an agricultural basin. This topic is of high relevance since glyphosate is the most applied pesticide in agricultural systems worldwide. We were able to quantify the seasonal variations of glyphosate that result mainly from endo-drift inputs, that is, from direct spraying either onto genetically modified (GM) crops (i.e., soybean an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
1
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(34 citation statements)
references
References 48 publications
3
21
1
9
Order By: Relevance
“…This explains the prevalence of herbicides in monitoring studies, given their wide use in extensive agriculture in the Pampas region; the most used chemicals within this group are glyphosate and atrazine (Leguizamón, 2014). This widespread use has led to finding them not only in the water column of freshwater ecosystems, but also in soils, sediments, groundwater and even in rainfall (Aparicio et al, 2013;Alonso et al, 2018;Okada et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…This explains the prevalence of herbicides in monitoring studies, given their wide use in extensive agriculture in the Pampas region; the most used chemicals within this group are glyphosate and atrazine (Leguizamón, 2014). This widespread use has led to finding them not only in the water column of freshwater ecosystems, but also in soils, sediments, groundwater and even in rainfall (Aparicio et al, 2013;Alonso et al, 2018;Okada et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Frequencies reported by other authors in watercourses of agricultural regions were generally lower but concentrations were several times higher [31,45,46]. Okada et al [47] monitored a stream southeast of the province of Buenos Aires (Argentina) and found glyphosate and AMPA in 28% and 50% of the samples, with a maximum concentration of 8.2 μg L −1 and 3.7 μg L −1 , respectively. On the other hand, Mac Loughlin et al [48] detected glyphosate and AMPA in a water body passing through a horticultural region in the Carnaval basin at concentrations up to 17.0 µg L −1 for glyphosate and 4.5 µg L −1 for AMPA, with a non-distinguishable behavior between seasons like our case.…”
Section: Glyphosate and Its Metabolite Ampamentioning
confidence: 88%
“…In groundwater from southeast of Buenos Aires, Okada et al [47] detected glyphosate and AMPA in 24% and 33% of the samples, with maximum levels of 8.5 μg L −1 and 1.9 μg L −1 , respectively. The lower frequencies and concentrations found in boreholes coincide with other studies [16,31], although Primost et al [46] did not detect these compounds in aquifers of the province of Entre Ríos with depths similar to Sachayoj, and Okada et al [47] did not find an association between depth and presence of glyphosate or AMPA.…”
Section: Glyphosate and Its Metabolite Ampamentioning
confidence: 99%
See 1 more Smart Citation
“…Typical ranges of GPS and PO 4 in soils are highly dependent on soil type and land use management. Maximum levels of GPS in soils from agriculturally intensive areas of Argentina range from 1.2 to 8.1 mg kg −1 soil (Primost et al, 2017; Okada et al, 2018), whereas total soil P typically ranges from 10 1 to 10 3 g P kg −1 soil (Kruse et al, 2015). Several studies demonstrated that GPS sorption by soils decreased in the presence of PO 4 .…”
mentioning
confidence: 99%